Assessing the role of extension, marketing and business development services on food security in the Comprehensive Agricultural Support Programme in Gauteng and KwaZulu-Natal provinces, South Africa - Terblanche, Fanie (University of Pretoria, 2025)
Dissertation (MSc Agric (Agricultural Extension))--University of Pretoria, 2025.